Precarity and clinical determinants of healthcare-seeking behaviour and antibiotic use in rural Laos and Thailand. Issue 12 (9th December 2020) - Haenssgen, Marco J; Charoenboon, Nutcha; Xayavong, Thipphaphone; Althaus, Thomas
Abstract : Background: The social determinants of health are a decisive yet persistently understudied area for tackling global health challenges like antimicrobial resistance (AMR). Precarity is one determinant whose importance is increasingly recognised, which we define here as 'a form of pernicious self-dependence that undermines individuals' control over their own lives and limits their ability to flexibly respond to crises'. We aimed to assess the relationship between precarity, other forms of deprivation and healthcare-seeking behaviour by asking, 'What is the impact of precarity, marginalisation and clinical presentation on healthcare-seeking behaviour?' and 'Do patients experiencing precarious livelihoods have clinically less advisable healthcare-seeking behaviour?' Methods: We used healthcare-seeking behaviour census survey data from rural Thailand and Laos, wherein five rural communities were surveyed two times over a period of 3 months (2-month recall period). Using descriptive statistical and multivariate logistic regression analysis on the illness level, we studied precarity alongside clinical presentation, marginalisation and facilitating solutions during an illness (eg, health-related phone use) as determinants of healthcare-seeking behaviour in the form of healthcare access and antibiotic use. Results: The data included 1421 illness episodes from 2066 villagers. Patients in precarious circumstances were up to 44.9 percentage points more likely to misuse antibiotics in the presence of situational facilitators (predicted antibiotic misuse: 6.2% (95% CI: 0.9% to 11.4%) vs 51.1% (95% CI: 16.6% to 85.5%) for precarious circumstances with/without facilitation). Marginalisation was linked to lower antibiotic use, but this did not translate into clinically more advisable behaviour. Clinical presentation played only a minor role in determining healthcare access and antibiotic use. Conclusions: This study underlines the importance of context and local livelihoods in tackling drug resistance. While supporting the growing emphasis on AMR-sensitive development policy, we call for future research to study systematically the healthcare-seeking behaviour impact of precarious livelihoods, social policy and community development initiatives. Trial registration number: NCT03241316 .